Ethylene regulates post-germination seedling growth in wheat through spatial and temporal modulation of ABA/GA balance. (24th December 2019) - Sun, Menghan; Tuan, Pham Anh; Izydorczyk, Marta S; Ayele, Belay T
Abstract : Ethylene controls post-germination starch degradation and seedling growth, but not radicle protrusion, in wheat through spatiotemporal alteration of the balance between abscisic acid and gibberellin. Abstract: This study aimed to gain insights into the molecular mechanisms underlying the role of ethylene in regulating germination and seedling growth in wheat by combining pharmacological, molecular, and metabolomics approaches. Our study showed that ethylene does not affect radicle protrusion but controls post-germination endospermic starch degradation through transcriptional regulation of specific α-amylase and α-glucosidase genes, and this effect is mediated by alteration of endospermic bioactive gibberellin (GA) levels, and GA sensitivity via expression of the GA signaling gene, TaGAMYB . Our data implicated ethylene as a positive regulator of embryo axis and coleoptile growth through transcriptional regulation of specific TaEXPA genes. These effects were associated with modulation of GA levels and sensitivity, through expression of GA metabolism ( TaGA20ox1, TaGA3ox2, and TaGA2ox6 ) and signaling ( TaGAMYB ) genes, respectively, and/or the abscisic acid (ABA) level and sensitivity, via expression of specific ABA metabolism ( TaNCED2 or TaCYP707A1 ) and signaling ( TaABI3 ) genes, respectively. Ethylene appeared to regulate the expression of TaEXPA3 and thereby root growth through its control of coleoptile ABA metabolism, and root ABA signaling via expression of TaABI3 and TaABI5 . These results show that spatiotemporal modulation of ABA/GA balance mediates the role of ethylene in regulating post-germination storage starch degradation and seedling growth in wheat.